Pengaruh Penggunaan Media Sosial Tiktok, Gaya Hidup dan Literasi Keuangan terhadap Perilaku Konsumtif Mahasiswa - Desitasari, Hanna Sebrina; Sumanto, Agus (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of TikTok social media usage, lifestyle, and financial literacy on consumer behavior among students of the Faculty of Economics and Business, State University of Malang using the SEM PLS method. The results of the study indicate that simultaneously and partially, TikTok social media usage, lifestyle, and financial literacy have a positive and significant influence on consumer behavior among students of the Faculty of Economics and Business, State University of Malang.